Characteristics of Fishing Vessels Owned by Fishermen from the Ujong Baroh Fish Landing Base (PPI) West Aceh Regency - Juhari Juhari; Yopi Novita; Budi Hascaryo Iskandar (Universitas Gadjah Mada, 2023)
Fishing vessel is one of an important thing among a fishing unit. All fishing activities are carried out on fishing vessel. In Indonesia, the shape and size of fishing vessels are vary, depending on the habits of the fishers and the area where the fishing vessels are built and operated. In West Aceh Regency, there are fishing vessels with various sizes. This study aims to identify the shape of fishing vessels measuring less than 10 gross tonnages (GT) at the Fish Landing Base (PPI) Ujong Baroh, West Aceh Regency. This identification is intended as a basis for reference in formulating fishing vessel design that follows the local wisdom of fishers in West Aceh Regency. This reference fishing vessel design can help the government and other parties provide aid fishing vessel for fishers in West Aceh Regency. The direct observation and measurement of fishing vessels were used in this research. Descriptive and numerical method used in analysis data. The number of sample was 27 fishing vessels consist of 10 sample with size of 1-5 GT and 17 with a size of 6-10 GT. The result show that fishing vessels in Aceh Barat District have a transom shape longitudinally and a round bottom or a round flat bottom shape transversely. All fishing vessels in West Aceh have a raked bow and a cruiser-shaped stern. The main dimensions ratio of group 6-10 GT is smaller than group 1-5 GT. The stability parameters of the two forms of fishing vessels follow the stability parameter values recommended by the International Maritime Organization (IMO). The static stability of fishing vessels with round flat bottom is better than round bottom.